The Relationship of Bank Competition and Risky Behavior in Indonesia - Riky Ikhwan,Telisa Falianty (International Conference on Industrial Revolution for Polytechnic Education, 2021)
This study aims to investigate whether the relationship between bank competition and bank risky behavior linear or non-linear. Using Indonesian bank-level data, we run an empirical analysis using GMM (Generalized Method of Moment) method. We find that bank competition has negative correlation with bank risky behavior, while positivecoefficient for the quadratic form of competition. This result provide strong support for non-linear relationship between bank competition and bank risky behavior in Indonesia.